Human Resource Risk Management Framework and Factors Influencing It - Golresan Kermani, Ameneh (2021)
Nowadays, the importance of human resource risk in organizations has greatly increased, and some thinkers refer to it as a core competency and a key responsibility for any human resource professional. Thus, given the importance of the subject of the present article, the aim of this study is to analyze the human resource risk management framework and the factors influencing it. In this regard, using the library method, human resource risk framework was analyzed from the perspective of management science thinkers of Paul and Milcher, Ernst and Young, Meyer, Maenpaa & Voutilainen, Rotarsko, Li and Zhang, Pandey.  Then, the factors influencing human resource risk management were identified and mentioned, and Stevens' human resource risk policies and procedures were presented. Then, the perception of risk and the factors influencing attention to risk and action for it were stated.  In the final section, theories related to risk perception were discussed in the form of the Wild risk-homeostasis theory (1982) and the Naatanen & Summak zero-risk theory (1976). Studies show that human resource risk management frameworks provide a conceptual model for the systematic development and planning of human resource risk management activities. They are also useful for assessing and evaluating the level of human resource risk. These frameworks provide the basis for planning, evaluating, and implementing human resource risk management.